Developing a Local Wisdom-Based E-Module to Enhance English Learning Motivation and Outcomes: An ADDIE-Driven Study in Merauke Regency - Harry Wilhelmus Joseph Rahawarin; Anik Ghufron (Journal of Innovation and Research in Primary Education, 2026)
The absence of culturally relevant instructional materials in English language teaching has been identified as a key factor contributing to low motivation and poor learning outcomes among students in culturally distinct regions of Indonesia. This study employed a Research and Development (R&D) approach using the ADDIE instructional design model to develop a local wisdom-based e-module for descriptive text learning among Grade X senior high school students in Merauke Regency, Papua. Expert validation, student response questionnaires, classroom observations, and a pretest–posttest control group design were used to assess the e-module's validity, practicality, and effectiveness. Data analysis involved descriptive statistics, N-Gain scores, and the Mann–Whitney U test. Expert validation yielded an overall score of 90% (Very Valid). Student responses confirmed high practicality, while the experimental group achieved a significantly higher mean N-Gain (0.56) than the control group (0.28; p < 0.05). Learning motivation improved across four of five measured dimensions, with persistence in learning scoring highest (M = 3.49). These findings demonstrate that the systematic integration of local wisdom into digital instructional materials enhances both motivation and achievement, affirming culturally responsive pedagogy as a substantive strategy for EFL instruction in linguistically diverse educational contexts.